DETERMINANTS, NEED ASSESSMENT AND SOLUTIONS OF YOUTH HOMELESSNESS IN MALAYSIA - Parveen, Kaur; Arif, Jawaid; Mohd Sohaimi, Esa; Muhammad Akram, Somroo; M. Ikram, Ul Haq (Siree Publications, 2020)
Homelessness is a global phenomenon that brings tyrannical consequences to the society. The purposes of this study are to investigate the determinants of youth homelessness, the needs of homeless youth population and probable solutions in solving this issue. Mixed method (including Qualitative and quantitative approaches) is applied in collecting the data and information. Convenience sampling and purposive sampling method are employed in selecting the samples. There are seven homeless respondents and ten volunteers participated in this research. The determinants of youth homelessness from the perspective of homeless youth and volunteers were investigated. Besides, the needs of homeless youth were studied. The framework and solutions in addressing youth homelessness were analyzed in the discussion. Researcher had come out with few recommendations in enhancing and modifying the framework in addressing this issue.